ANALYSIS OF THE NONLINEAR DIFFUSION SYSTEM WITH NONLINEAR BOUNDARY CONDITIONS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In this paper, we consider the solvability and unsolvability of solutions of a nonlinear diffusion system with a source and nonlinear boundary conditions in the case of slow diffusion. Establishing numerous self-similar super-solutions and sub-solutions for the nonlinear diffusion system.